The Use and Abuse of Patent Reexamination: Sham Petitioning Before the USPTO - Mercado, Raymond A. (Science and Technology Law Review, 2011)
This article investigates the susceptibility of the patent reexamination process to abuse and argues that “sham petitioning” in the reexamination context threatens to undermine the quid pro quo of the patent system, jeopardizing the objectives of innovation and disclosure by weakening the incentive of the patent right. Since reexamination casts a cloud on the validity of a patent and harms enforceability, the patent holder subject to such a proceeding instigated under false pretenses can be deprived of the economic benefits his patent should otherwise have afforded him. In an effort to help craft a solution, the article explores the ways in which reexamination is vulnerable to abuse and looks closely at several instances of alleged misconduct. It contends that state tort remedies provide patent holders subject to unwarranted proceedings an adequate recourse for harms suffered. It also comments on a recent case in which the Federal Circuit was asked to consider whether such remedies are preempted, arguing that the court’s surprising decision to affirm without opinion perpetuates uncertainty throughout the patent system and evades important questions of first impression. Finally, a number of proposals are offered with a view to curbing abuse in current and future variants of the reexamination process.